A new ceramide and other constituents from the fruits of Ficus lutea Vahl (Moraceae) and their chemotaxonomic significance. (February 2023) - Sonfack Fozeng, Herman D.; Nanfack Donfack, Arno R.; Tchuente Tchuenmogne, Marthe A.; Tchegnitegni, Billy Toussie; Tsepeupon Matchide, Marie G.; Matheuda, Elodie Gaële; Dzatie Djoumbissie, Raymonde A.; Mba Nguekeu, Yves M.; Ngouela, Silvère Augustin; Shaiq Ali, Muhammad; Awouafack, Maurice Ducret; Tene, Mathieu
Abstract: A new ceramide named luteaceramide (1 ), along with sixteen known compounds including 3 α -hydroxy-27- p -( E )-coumaroyloxyursan-12-en-28-oic acid (2 ), 3 α -hydroxy-27- p -( Z )-coumaroyloxyursan-12-en-28-oic acid (3 ), 3- O -acetyl- α -amyrin (4 ), lupeol (5 ), a mixture of β -sitosterol (6 ) and stigmasterol (7 ), 24-methylenecycloartenol (8 ), hexacosanol (9 ), ergosterol 5 α, 8 α -endoperoxide (10 ), hexatriacontan-1-ol (11 ), 3 β -acetoxy-1 β, 11α-dihydroxyolean-12-ene (12 ), palmitic acid (13 ), tormentic acid (14 ), alphitolic acid (15 ), β -sitosterol-3-O- β -D glucopyranoside (16 ), and ursolazuroside 1 (17 ) were obtained after phytochemical investigation of the methanol extract of the fruits of Ficus lutea . The structure of the new compound was elucidated by analyses of their spectroscopic data including 1D and 2D-NMR, HREI-MS and chemical conversions. The MeOH crude extract had weak activity against Proteus mirabilis (MIC 2.5 mg/mL). Luteaceramide (1 ), lupeol (5 ) and hexacosanol (9 ) showed a moderate antibacterial activity against Escherichia coli with MIC ranging from 31 to 63 μg/mL while 1 was weakly active against Staphylococcus aureus, Enterococcus faecalis, and P. mirabilis with MIC between 125 and 250 μg/mL. Compounds 2, 3, 12, 14, 15, and 17 are also reported for the first time from the genus Ficus . The chemotaxonomic significance of the isolated compounds was summarized. Our results on the isolation of a new ceramide (1 ), triterpenoids of ursan (2 –4, 14 and 17 )-, lupan (5 and 15 )-, oleanan (12 )-, and cycloartan (8 )-types, steroids (6, 7, 10 and 16 ), alcohols (9 and 11 ), and a fatty acid (13 ) from F. lutea Vahl are in good agreement with the classification and the chemotaxonomy of this species for the genus Ficus and for the family Moraceae. The phytochemical analyses of plant species of the genus Ficus in most of the cases provided the isolation of ceramides. This class of secondary metabolites could be considered as one of the markers of the genus Ficus . Graphical abstract: Image 1 Highlights: Seventeen compounds were obtained from the fruits of Ficus lutea Vahl. Characterization of a new ceramide while six known compounds were new in F. lutea. The chemotaxonomic significance of the isolated compounds was summarized. Luteaceramide had moderate antibacterial activity against Escherichia coli .